2018
DOI: 10.1155/2018/4512137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient-Dependent and Trauma-Dependent Risk Factors for Persistent Brachial Plexus Injury after Shoulder Dislocation

Abstract: Brachial plexus injuries (BPIs) caused by shoulder dislocation usually have a transient character and tend to resolve spontaneously. However, in some patients the symptoms can persist and require operative intervention. This work aims to determine the risk factors for persistent BPIs resulting from shoulder dislocation. The study comprised 73 patients (58 men, 15 women; mean age: 50 years) treated operatively between the years 2000 and 2016 for persistent BPIs resulting from shoulder dislocation. Patient age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
2
29
1
1
Order By: Relevance
“…In the study by Robinson et al, injury to the axillary nerve alone was more common in young individuals and as a result of high-energy trauma, while complex neurological deficits were associated with older age, female sex and low-energy fall [5]. Another study confirmed that single nerve injury is more likely to be a result of high-energy trauma in a younger patient, while multiple nerve injury would be a result of lowenergy fall in an elderly patient [19]. In the previously cited study by Robinson et al, percentage of multiple nerve lesions was significantly higher in the group with other associated injuries (rotator cuff tear (RCT)/GTF) [5].…”
Section: Affection Of Particular Nervesmentioning
confidence: 91%
See 4 more Smart Citations
“…In the study by Robinson et al, injury to the axillary nerve alone was more common in young individuals and as a result of high-energy trauma, while complex neurological deficits were associated with older age, female sex and low-energy fall [5]. Another study confirmed that single nerve injury is more likely to be a result of high-energy trauma in a younger patient, while multiple nerve injury would be a result of lowenergy fall in an elderly patient [19]. In the previously cited study by Robinson et al, percentage of multiple nerve lesions was significantly higher in the group with other associated injuries (rotator cuff tear (RCT)/GTF) [5].…”
Section: Affection Of Particular Nervesmentioning
confidence: 91%
“…Brachial plexus injury was found in 1.2% of multitrauma patients in the study by Midha et al, with shoulder dislocation being responsible for 7% of closed BPIs [53]. Males predominated in all large patient groups (M/F from 1.3:1 in the study by Robinson et al to 6.3:1 among the patients studied by Fox et al) (Table 1) [5,[18][19][20][21][22].…”
Section: Incidencementioning
confidence: 99%
See 3 more Smart Citations